How Does Financial Self-Efficacy Affect Financial Behavior and Financial Well-Being? Evidence from a Gender Perspective - Lambok Nababan; Jhason Kristian Lee (Jurnal Maksipreneur, 2026)
This study examines the influence of financial self-efficacy (FSE) on financial behavior and financial well-being, with a particular focus on gender differences. It investigates the extent to which individuals' confidence in their financial management skills influences behaviors such as budgeting and, in turn, their overall financial well-being. It emphasizes that individuals with higher FSE tend to make more informed financial decisions, which in turn result in greater financial security. The study also examines the differential impacts of FSE on men and women, revealing that women are more profoundly affected by their financial self-confidence in financial management and in attaining enhanced financial well-being than men. These findings indicate the need for gender-sensitive financial education programs to empower women, especially in long-term financial planning and investing. The study also suggests that improving FSE through targeted financial education programs can lead to better financial management for both men and women, while considering cultural and social factors.